Effect of seedling age on productivity and profitability in traditional rice landraces - Ashraf, A Mohammed; Lokanadan, Subbalakshmi (ORYZA-An International Journal of Rice, 2022)
A field experiment was conducted at Tamil Nadu Agricultural University, with an objective to study the effect of seedling age on productivity and profitability in rice landraces under irrigated rice ecosystem. The experiment was laid out in split plot design with three replications. The treatments in main plot were three age of seedlings viz., 15, 20 and 25 days old seedlings and in sub plot eight rice landraces viz., Chandikar, Kuliyadichan, Kuruvaikalanjiyam, Norungan, Nootripathu, Black Kavuni, Red Kavuni, Njavara and CO(R) 50 (one high yielding variety). Observations were recorded on growth parameters such as plant height, tiller numbers and dry matter production. The yield attributes like productive tillers, total spikelet, filled grains, unfilled grains, spikelet sterility percentage, thousand grain weight, grain yield and straw yield were recorded at the time of harvest. From the study it was observed that 15 days old seedlings in all the eight rice landraces and one high yielding variety, recorded higher growth and yield attributes. In rice landraces, Red Kavuni recorded higher grain, straw yield and B:C ratio. Based on quality parameters, CO(R) 50 rice variety and landraces viz., Red Kavuni, Black Kavuni, Nootripathu, Chandikar recorded optimum values and were suitable for cooking purpose.